Ten years of Howie Severino - Severino, Horacio; Flores, Marissa L. (GMA Network, 2007)
"Babalik na si Ma'am" - Former maestras turned domestic helpers in Hong Kong finally come home to teach. "Pitong araw, pitong gabi" - Howie journeys around Luzon about assorted Pinoy transport. "From Iraq with love" - On the eve of war, Howie encounters Iraq before it is changed forever. "Pantasya ng bayan" - The search for the first Darna movie leads Howie to exotic Thailand. " Unggoy" - A deceptive peace reigns in Mindanao where wild monkeys and spiritual people live together. "Best friend" - An illiterate old man and his clever dog travel in search of his little boy. "Biyaheng EDSA" - Howie takes a meandering walk along the nation's highway to greatness. "Huling hala bira!" - Facing demolition, residents living under the rail tracks in Manila prepare to dance at their last Ati-Atihan Festival. "No story is worth dying for" - Howie covers the famous siege of Lamitan and together with a dozen journalists, gets caught in the crossfire. "Lolo ng San Francisco" - An aging war veteran living alone in America is the center of a colorful street world.